P-OGC80 The effect of COVID -19 on new diagnosis oesophagogastric cancer patients in the UK: A single-centre experience. (16th December 2021) - McQuillan, Patrick; Ahmed, Salman; Navidi, Maziar; Hayes, Nick; Wahed, Shajahan; Immanual, Arul; Phillips, Alex
Abstract: Background: Covid-19 has had a devastating global impact and resulted in over 4.4 million directly attributed deaths. The UK entered lockdown in March 2020, redistributing its medical workforce and resources. Early estimations suggested at least 4700 extra cancer deaths at 5 years if there was a 3-month delay to surgery. Delays to diagnosis and treatment for osophagogastric (OG) cancers can be particularly detrimental to survival. The aim of this study is to assess the impact of Covid-19 on new cancer referrals to a centralised UK OG cancer centre, including presentation, decision making and treatment. Methods: Patients with OG cancer referred to a tertiary, high-volume centre between March 2019 and March 2021 were reviewed. Patients were stratified into Pre-covid (March 2019-March 2020) and Covid (March 2020-2021) cohorts. Number of new referrals, clinical stage, treatment decision, and time to treatment were compared for gastric adenocarcinoma (GA), oesophagogastric-junction adenocarcinoma (OGJA), oesophageal adenocarcinoma (OA) and oesophageal SCC (OSCC). Results: There was an 11% reduction in new cancer referrals (485 vs 431). GA, OGJA and OA did not have significant change in treatment intent, although there was a significant increase in the decision for definitive non-surgical treatment of OA (P = 0.046). GA and OA patients had a small, but significant increase in mean clinical stage at presentation (P < 0.05). There was no increase in time to treatment for GA, OGJA and OA. A significantly higher proportion of OSCC patients were given curative intent treatment in the Covid-19 cohort (P = 0.0006) however, this was accompanied with an increased time to treatment commencement (35.8 days vs 27.9 days P = 0.0198). Conclusions: This high-volume centre has seen a reduction in new cancer referrals since the first UK lockdown. This was associated with a small, but significant, increase in clinical stage of GA and OA at presentation. This may represent an early indication of excess oesophagogastric cancer deaths due to the impact of Covid-19. This data also confirms initial results showing that oncological decisions were not compromised, although Covid-19 remains a dynamic challenge.